Cancer care in times of conflict: Treatment of patients from Afghanistan, in Pakistan - Mahmood, Shahid; Khawaja, Shehryar Nasir; Yusuf, Muhammed Aasim (Frontiers in Oncology, 2023)
Introduction: Afghanistan has been in a near-continuous armed conflict, which has degraded the country’s health infrastructure. Due to this, Afghans have opted to seek cancer treatment in Pakistan. This manuscript aims to understand the complex cancer journey of patients from Afghanistan seeking care in the largest tertiary care cancer institutions in Pakistan. Methods: This retrospective study explores the demographics, epidemiology and outcomes of Afghan cancer patients treated at the Shaukat Khanum Memorial Cancer Hospital and Research Centres (SKMCH&RC) in Lahore and Peshawar, Pakistan, over the period from 1995 to June 2022. Results: A total of 6,370 patients from Afghanistan have undergone cancer care since 1995. The mean age at presentation was 40.7 years, 57% were male, and 87% were adults >19 years. Close to 30% of these patients came from Kabul and Nangarhar districts. 56% of all patients presented with stage III or IV disease. 34% of adult patients achieved a complete response to treatment, but more than half of all patients have since been lost to follow-up. Children generally had better outcomes, with 43% showing a complete response to treatment. Discussion: The cancer journey for these patients remains long and difficult and the inability to ensure follow-up in so many remains frustrating for both patients and providers. The lack of a cancer infrastructure in Afghanistan after decades of conflict, means that policymakers need to develop and support alternative systems and structures to provide post-conflict domestic and cross-border cancer care.